The Markers Auxiliary in Distinguishing between Nodal Nevi and Melanoma Metastases - Kuźbicki, Łukasz (Current Medicinal Chemistry, 2025)
Nodal nevus (NN) and melanoma metastasis (MM) have distinct biological and prognostic significance. They are characterized by different cytomorphological features and varying intranodal localization. However, in some cases, distinguishing them in standard hematoxylin and eosin-stained specimens can be challenging. The aim of this review is to evaluate the usefulness of markers in the diagnosis of NN and MM. The expression of selected markers in NN and MM was examined immunohistochemically in 27 studies. The frequency of HMB-45 and PRAME staining was significantly higher, while p16 was lower in MM than in NN. A slight increase of Ki-67 and decrease of 5-hmC expression in MM compared to NN were also observed. Meanwhile, staining of Melan-A/Mart-1, S-100, and SOX-10 was similar in NN and MM. However, none of the markers applied was completely specific for melanocytes. Although PRAME proved to have the strongest diagnostic potential, it was also detectable in other cell types, especially in lymphocytes and some breast cancers. Immunohistochemical staining of PRAME, HMB-45, and p16 may aid the diagnosis of NN and MM. Ki-67 and 5-hmC may also be of promising significance, whereas the expression of Melan-A/Mart-1, S-100, and SOX-10 does not allow distinguishing NN from MM.
Keywords: diagnosis